Integrasi Telegraf, InfluxDB OSS V2, dan Grafana dalam Monitoring Trafik Jaringan berbasis NetFlow - Firdaus (mijournal.org, 2025)
In modern networking, traffic monitoring is essential for maintaining the stability, efficiency, and security of network systems. One of the protocols used for traffic monitoring is NetFlow. However, an efficient system is needed to collect, store, and visualize NetFlow data. This study discusses the implementation of the open-source TIG stack (Telegraf, InfluxDB, Grafana) to build a NetFlow-based network traffic monitoring system. The system uses Telegraf as the data collector, InfluxDB as the time-series data storage, and Grafana as the visualization tool. With this approach, traffic data can be visualized in real-time and historically through an interactive dashboard. This research uses an experimental method within a Docker-based virtualization environment. The test results show that the system is effective for monitoring network traffic in small to medium-scale